Soft Tissue Profile Analysis for Iraqi Patients with β- Thalassemia Major (Mustansiria Dental Journal, 2018)
The facial appearance of patients with β-thalassemia major is readily recognizableso that soft tissue profile analysis is presented in this study.The aim of the study is concerned about the analysis of soft tissue profilemorphology in a group of patients having β-thalassemia major and to record thepossible differences between both thalassemic genders and to investigate thedifferences in the soft tissue morphology between thalassemic patients and nonthalassemic normal subjectsThe material of this study consisted from lateral cephalometric radiographs for(40) thalassemic patients aged 15-17 years and (40) cephalometric radiographs fornon thalassemic normal subjects were obtained for analyzing soft tissue profilemorphologyThe results showed that there were no significant differences between thalassemicmales and females but the soft tissue profile morphology for thalassemic patientsmostly different from normal subjects which characterized by convex profile.Thalassemic patients have a soft tissue profile morphology mostly different fromnormal's that characterized by smaller nasal dimensions, short and everted upper lipand thicker lower lip which giving them the appearance of convex profile.